Resistance in Vancomycin-Resistant Enterococci (2020)
Abstract Serious infections owing to vancomycin-resistant enterococci have historically proven to be difficult clinical cases, requiring combination therapy and management of treatment-related toxicity. Despite the introduction of new antibiotics with activity against vancomycin-resistant enterococci to the therapeutic armamentarium, significant challenges remain. An understanding of the factors driving the emergence of resistance in vancomycin-resistant enterococci, the dynamics of gastrointestinal colonization and microbiota-mediated colonization resistance, and the mechanisms of resistance to the currently available therapeutics will permit clinicians to be better prepared to tackle these challenging hospital-associated pathogens.